História, autobiografia e ficção : a ilusão da realidade em partes de África - Pires, Nayara Meneguetti (2016)
Partes de África, by the Portuguese writer Helder Macedo, is intriguing due to fragmentation and profusion of speeches that assembles when unites diverse voices, memory, history, autobiography and fiction in what the narrator calls a mosaic-inlaid mirrors. If on the one hand the narrative fragmentation is not new, on the other, the mirroring undertaken between its various pieces inserts the narrative in an undecidable place, refusing theories and binarisms in which the colonial world was engineered. In addition, there is a constant flirtation with referentiality, highlighted by the metaficcionality of a narrator self-conscious of the relativity of truth. For this reason, we pursue the hypothesis that Partes de África refuses the traditional speech forms which are identified with the idea of the writing’s ability to apprehend the truth about a subject or about his own time, as is the case with traditional history, the autobiography or the novels of eighteenth and nineteenth century. It is evident in this novel, a narrative way of relating to reality that is typical of the contemporary world, which conceives the notion of subject and history as categories constantly changing because they are hopelessly being modified by the future. Subject and history are an eternal construction and, to show this dynamic character, the narrator makes use of strategies used by traditional speeches to create an illusion of reality just to destabilize them, presenting them rather an effect of reality.